Longitudinal effects of stress in an academic context on psychological well-being, physiological markers, health behaviors, and academic performance in university students - Juan Camilo Benítez-Agudelo; Dayana Restrepo; Eduardo Navarro-Jimenez; Vicente Javier Clemente-Suárez (BMC Psychology)
Abstract Background Stress in academic settings arises from the interplay between perceived demands such as exams, deadlines, and academic workload and an individual’s coping resources. While academic stress (AS) is frequently examined as a separate construct, the stress encountered in an academic environment encompasses both academic and non-academic stressors that students face throughout their university experience. This study examined the longitudinal associations between stress in an academic context on key psychological, physiological, and behavioral variables in university students. Methods A longitudinal study was conducted with 115 Colombian psychology students aged 16 to 35 years, evaluated at the beginning and end of an academic semester. Variables were measured using validated psychometric questionnaires, including the Big Five inventory, the Zung Depression Scale, the UCLA Loneliness Scale, the State-Trait Anxiety Inventory (STAI), the Acceptance and Action Questionnaire (AAQ-II), the Perceived Stress Scale-4 (PSS-4). Behavioral data, such as physical activity, sleep patterns, and academic performance, were also recorded. Heart rate variability (HRV), a widely used physiological marker of autonomic nervous system function and stress regulation, was assessed. Paired t-tests were used to compare baseline and final measurements, and multiple linear regression determined predictors of academic performance. Results Longitudinal analysis revealed significant declines in sleep duration, quality, and heart rate variability (HRV), alongside increased anxiety and depressive symptoms, indicating heightened stress and autonomic dysregulation. Despite these adverse effects, academic performance improved. This pattern suggests a complex association where higher achievement coincided with declining well-being markers. Regression models identified depressive symptoms as negative predictors of performance, while greater HRV (SD1, PNN50) and balanced autonomic activity were positively associated with academic performance. Conclusions This study examines the longitudinal effects of stress within an academic environment on the psychological, physiological, and behavioral outcomes of university students. The findings showed compromised sleep patterns, changes in autonomic regulation, and mental health indicators; nevertheless, an increase in academic performance is also noted. However, this enhancement coincides with heightened levels of anxiety, depressive symptoms, and physiological dysregulation. These results highlight the necessity for targeted interventions aimed at fostering resilience and promoting a holistic sense of well-being.